Comprehensive Characterization of Simple Sequence Repeats in Eggplant (Solanum melongena L.) Genome and Construction of a Web Resource - Portis, Ezio; Lanteri, Sergio; Barchi, Lorenzo; Portis, Flavio; Valente, Luisa; Toppino, Laura; Rotino, Giuseppe L.; Acquadro, Alberto (Frontiers in Plant Science, 2018)
The recently acquired high quality genome sequence of eggplant (Solanum melongena) has been used to catalog the genome's content of simple sequence repeat (SSR) markers. Nearly 133,000 perfect SSRs were revealed, equivalent to an overall density across the genome of 125.5 SSRs/Mbp, but some 178,400 imperfect SSRs were also identified. About 15.6% of these SSRs were complex (two stretches of repeats separated by <100 nt). Some 43% and 37% of the SSRs were composed of di- and trinucleotide motifs respectively. The SSRs were categorized for the numbers of repeats present, their overall length and were allocated to their linkage group. A total of 2,449 perfect and 3,524 imperfect SSRs were respectively present in 2,086 and 2,924 genes, corresponding to an overall density across the gene space of 18.5 and 26.7 SSRs/Mbp for perfect and imperfect motifs respectively. Based on a gene ontology approach, a putative function, to genes harboring at least one SSR was assigned. A database, named “Eggplant Microsatellite DataBase” (EgMiDB), was developed. It facilitates the retrieval of SSR markers in relation to their genomic location, genomic vs genic context, perfect vs imperfect repeat, motif type, motif sequence as well as repeat number, and suggests the forward and reverse primers. The SSR markers were validated, via an in silico based PCR analysis, adopting three assembled transcriptomes and two CDS set from genomic projects, derived from contrasting eggplant accessions, as templates.